2021
DOI: 10.22541/au.161597686.60503163/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human Cardiac Ischemia-Reperfusion Injury: Blunted Stress Response with Age

Abstract: Background & Aim: Autophagy is a cytoprotective recycling mechanism, capable of digesting dysfunctional cellular components, and this process is associated with pro-survival outcomes. Autophagy may decline in the aging myocardium, thereby contributing to cardiac dysfunction. However, it remains to be established how autophagy responds to ischemia-reperfusion stress with age. Methods: Samples from the right atrium were collected from young (≤50 years; n=5) and aged (≥70 years; n=11) patients prior to and im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…analyzed right atrial samples from young (≤50 years) and aged (≥70 years) patients just before and immediately after cardioplegic arrest during CABG surgery, a model of human I/R injury. 15 These authors observed a decline in mitochondrial content in aged myocardium. In response to I/R challenge, the mitochondrial marker COX-I was upregulated in young, but not aged patients.…”
Section: Aging Autophagy Ischemia-reperfusion Mitophagymentioning
confidence: 96%
See 1 more Smart Citation
“…analyzed right atrial samples from young (≤50 years) and aged (≥70 years) patients just before and immediately after cardioplegic arrest during CABG surgery, a model of human I/R injury. 15 These authors observed a decline in mitochondrial content in aged myocardium. In response to I/R challenge, the mitochondrial marker COX-I was upregulated in young, but not aged patients.…”
Section: Aging Autophagy Ischemia-reperfusion Mitophagymentioning
confidence: 96%
“…In this issue of Journal of Cardiac Surgery, Oliveira et al analyzed right atrial samples from young (≤50 years) and aged (≥70 years) patients just before and immediately after cardioplegic arrest during CABG surgery, a model of human I/R injury 15 . These authors observed a decline in mitochondrial content in aged myocardium.…”
mentioning
confidence: 99%